3(2t-6)=2(3r-9)

Simple and best practice solution for 3(2t-6)=2(3r-9) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(2t-6)=2(3r-9) equation:


Simplifying
3(2t + -6) = 2(3r + -9)

Reorder the terms:
3(-6 + 2t) = 2(3r + -9)
(-6 * 3 + 2t * 3) = 2(3r + -9)
(-18 + 6t) = 2(3r + -9)

Reorder the terms:
-18 + 6t = 2(-9 + 3r)
-18 + 6t = (-9 * 2 + 3r * 2)
-18 + 6t = (-18 + 6r)

Add '18' to each side of the equation.
-18 + 18 + 6t = -18 + 18 + 6r

Combine like terms: -18 + 18 = 0
0 + 6t = -18 + 18 + 6r
6t = -18 + 18 + 6r

Combine like terms: -18 + 18 = 0
6t = 0 + 6r
6t = 6r

Solving
6t = 6r

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Divide each side by '6'.
t = r

Simplifying
t = r

See similar equations:

| 5x+5(4x+12)=10 | | 2(x-3)=1/2x | | 3(n+1)-2n=0 | | -2z+13z+13z-20z=-20 | | 0=4+2n | | 13+b=-4 | | 4/7y-8=2/7y-10 | | 2x-14y=22 | | 3(4x+5)-3y=-15 | | 8-2x=-13 | | 8(-2i)(-5-4i)= | | (8(-3)-1)-(-3)+3= | | 82(0.006889-x^2)=2x | | 3x-3y=4x+5 | | 19=4-2x | | 32x-4=3 | | -16a+11a+7a=-16 | | w/- | | 82(0.006888-x^2)=2x | | -16+y=5 | | 6-a=10-9 | | 4(x-6)=21 | | -3p+13p+14=-16 | | 2*.2-3+7+7+3*.2-10= | | (3x+3)=(4x-5) | | 15(t+2)2+9t=-90 | | 2x+5(.3-2.3)=3 | | r=0.301 | | 12+6r=-4r-5-7r | | y=10*x+500 | | -5x+4-3(x-1)=-3x-(4x-1)+3 | | 13q-12q+q-2=12 |

Equations solver categories